Transcendental Communication in Indigenous Peoples, Case Study of Kuncen's Trasendental Communication Function With Banokeling Spirits for Banokeling Indigenous Communities - Beny Wijarnako; Ana Andriani; Asih Ernawati (Proceedings Series on Social Sciences & Humanities, 2023)
Examining the existence of traditional leadership can reveal a cultural bias related to irrational human actions related to supernatural beings, which are goal-oriented to meet the needs of their members. The cult of Eyang Banokeling is so strong in the Banokeling indigenous community, although Eyang Banokeling has long since died but the spirits that reside in the sacred burial placed in the Kedaton area are still strongly felt today, the Kedaton area is also a center of transcendental communication of the successor kuncens who are related to the spirits of Eyang Banokeling in fulfilling all the celebrations of this indigenous community, as well as the existence of Kyai Kuncen as a liaison for the spirits of Eyang Banokeling as well as the presence of The Banokeling Spirits as well as the presence of Kyai Kuncen as a liaison for the spirits of Eyang Banokeling as well as the liaison of the spirits of Eyang Banokeling as well as as indigenous leaders means a lot in this indigenous community. This study will try to examine the meaning of transcendental communication carried out by Kyai Kuncen for the indigenous people of Banokeling. The research was conducted with a qualitative approach using the case study method, which focuses attention on one particular object raised as a case. In the case study method, facts are achieved through the assessment of the connectedness of evidence from several data sources at once, namely documents, recordings, observations, open interviews, focused interviews, structured interviews and field surveys, so that the true meaning of Kyai Kuncen's transcendental communication function with the spirit of Eyang Banokeling is revealed for the Banokeling Indigenous Community.